Egitomania, imaginário social e a imprensa inglesa do século XIX (1866-1876) - Santiago, Bárbara Isadora Resek (2023)
The present dissertation analysed the expansion of the phenomenon of Egyptomania through the role of the British magazine press between the years 1866 and 1876 and sought to problematize the importance of Egyptomania in the formation of the Eurocentric social imaginary in England at the time. The dissertation was divided into three parts, and, at first in chapter entitled The English, the Press and Egyptomania, the discussion addressed the origin of the term and the meanings of the phenomenon of Egyptomania, as well as the expansion of the Victorian press and its importance in the conformation of public communication at the time and in the formation of a mass public. Then, in chapter The British Magazine Press: Belgravia, Bow Bells and The Athenaeum, an analysis was carried out regarding the editorial projects and conditions of production, circulation and diffusion of the three magazines object of this research, that is, Belgravia, Bow Bells and The Athenaeum, which were founded in the 19th century and brought literary publications in chapters and scientific, historical, everyday, literary articles, in addition to identifying the breadth of narratives related to ancient Egypt present in such publications. Finally, in chapter Egypt in paper representations, the references to ancient Egypt present in each of the magazines were examined in more detail and, through the concepts of imaginary and orientalism, it was discussed how Egypt's past impacts readers in Victorian England, thus seeking to problematize the strength of magazines in the constitution of a certain imaginary about ancient Egypt in different layers of the reading public at the time